Primary leiomyosarcoma of the thoracic aorta. Case report and review of literature - Drozd-Lula, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2001)
The subject of this article is a 73-year old woman with primary leiomyosarcoma of the thoracic aorta which gave via arteriae multiple metastases to the skin and bones of inferior extremities. Reviewed was the literature concerning this unusual localisation of leiomyosarcoma.